"Otherwise We Would Be like an Island": A Phenomenological Understanding of Intergenerational Engagement Aimed at Reducing Social Isolation. Issue 2 (3rd April 2023) - Steward, Andrew; McDevitt, Kimberly
ABSTRACT: This phenomenological study involved individual, unstructured interviews with older adults. Eleven participants were recruited from independent living, assisted living, and community center settings. The study was guided by three overarching research aims: 1) To understand if and how intergenerational engagement helps reduce social isolation and loneliness for older adults 2) to understand how intergenerational experiences may have changed over time, and 3) to identify specific barriers, facilitators, benefits, and best practices of intergenerational engagement among older adults. Results revealed important themes related to increasing age segregation, the potential impacts of internalized ageism, and a need for small group or one-on-one intergenerational opportunities.